Polymorphisms of GLP-1 Receptor Gene and Response to GLP-1 Analogue in Patients with Poorly Controlled Type 2 Diabetes - Chia-Hung Lin; Yun-Shien Lee; Yu-Yao Huang; Sheng-Hwu Hsieh; Zih-Syuan Chen; Chi-Neu Tsai (Journal of Diabetes Research)
Aim. The relationship between genetic polymorphisms of the glucagon-like peptide-1 (GLP-1) receptor (GLP1R) gene and unresponsiveness to GLP-1 analogue treatment in patients with poorly controlled type 2 diabetes mellitus (DM) is unclear. Methods. Thirty-six patients with poorly controlled type 2 DM were enrolled and they received six days of continuous subcutaneous insulin infusion for this study. After the normalization of blood glucose in the first 3 days, the patients then received a combination therapy with injections of the GLP-1 analogue, exenatide, for another 3 days. All 13 exons and intron-exon boundaries of the GLP1R gene were amplified to investigate the association. Results. The short tandem repeat at 8GA/7GA (rs5875654) had complete linkage disequilibrium (LD, with r2=1) with single nucleotide polymorphism (SNP) rs761386. Quantitative trait loci analysis of GLP1R gene variation with clinical response of GLP1 analogue showed the missense rs3765467 and rs761386 significantly associated with changes in the standard deviation of plasma glucose (SDPGbaseline-SDPGtreatment with GLP-1 analogue) (P=0.041 and 0.019, resp.). The reported P values became insignificant after multiple testing adjustments. Conclusion. The variable response to the GLP-1 analogue was not statistically correlated with polymorphisms of the GLP1R gene in patients with poorly controlled type 2 DM.